Prototyping the implementation of a suicide prevention protocol in primary care settings using PDSA cycles: a mixed method study - Minian, Nadia; Gayapersad, Allison; Coroiu, Adina; Dragonetti, Rosa; Zawertailo, Laurie; Zaheer, Juveria; O’Neill, Braden; Lange, Shannon; Thomson, Nicole; Crawford, Allison; Kennedy, Sidney H.; Selby, Peter (Frontiers in Psychiatry, 2024)
Introduction: In Canada, approximately 4,500 individuals die by suicide annually. About 45% of suicide decedents had contact with their primary care provider within the month prior to their death. Current versus never smokers have an 81% increased risk of death by suicide. Those who smoke have additional risks for suicide such as depression, chronic pain, alcohol and other substance use. They are more likely to experience adverse social determinants of health. Taken together, this suggests that smoking cessation programs in primary care could be facilitators of suicide prevention, but this has not been studied. Study objectives were to: understand barriers/facilitators to implementing a suicide prevention protocol within a smoking cessation program (STOP program), deployed by an academic mental health and addiction treatment hospital, in primary care clinics, and; develop and test implementation strategies to facilitate uptake of suicide screening and assessment in primary care clinics across Ontario. Methods: The study employed a three-phase sequential mixed-method design. Phase 1: Conducted interviews guided by the Consolidated Framework for Implementation Research exploring barriers to implementing a suicide prevention protocol. Phase 2: Performed consensus discussions to map barriers to implementation strategies using the Expert Recommendations for Implementing Change tool and rank barriers by relevance. Phase 3: Evaluated the feasibility and acceptability of implementation strategies using Plan Do Study Act cycles. Results: Eleven health care providers and four research assistants identified a lack of training, and the need of better educational materials as implementation barriers. Participants endorsed and tested the top three ranked implementation strategies: a webinar, adding a preamble before depression survey questions, an infographic. After participating in the webinar and reviewing the educational materials, all participants endorsed the three strategies as acceptable/very acceptable and feasible/very feasible. Conclusion: Although there are barriers to implementing a suicide prevention protocol within primary care, it is possible to overcome them with strategies deemed both acceptable and feasible. These results offer promising practice solutions to implement a suicide prevention protocol in smoking cessation programs delivered in primary care settings. Future efforts should track implementation of these strategies, measure outcomes including provider confidence, self-efficacy, and knowledge, and patient outcomes.